Reviewers of this issue Vol.14(1) - Editor, The (Nepal Journal of Science and Technology, 2013)
Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) DOI: http://dx.doi.org/10.3126/njst.v14i1.8949